2018
DOI: 10.15561/20755279.2018.0606
|View full text |Cite
|
Sign up to set email alerts
|

Does the weight of basketball shoes affect speed and jumping performance?

Abstract: Purpose: The objective of this study was to analyze the effect of different weights of basketball shoes on speed and jumping performance in male basketball players. Methods: 20 male basketball players in two groups, as eyes open (n:10) and eyes closed (n:10) participated in the study. The two groups performed vertical jump (VJ) and 10m sprint tests with three different weights of shoes (light, 352g; medium, 510g; heavy, 637g). The data were analyzed with Friedman repeated measurements variance analysis. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This finding has been supported by other similar studies. Recent study by Köse ( 2018 ) verified that the weight difference of 285 g between two shoes has shown a significant effect on 10-m sprint performance. In another study on basketball shoe, it was reported that the shoe within 20% of weight difference did not significantly influence the sprint and cutting performances (Worobets and Wannop, 2015 ).…”
Section: Discussionmentioning
confidence: 98%
“…This finding has been supported by other similar studies. Recent study by Köse ( 2018 ) verified that the weight difference of 285 g between two shoes has shown a significant effect on 10-m sprint performance. In another study on basketball shoe, it was reported that the shoe within 20% of weight difference did not significantly influence the sprint and cutting performances (Worobets and Wannop, 2015 ).…”
Section: Discussionmentioning
confidence: 98%